1989
DOI: 10.1254/jjp.49.297
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electric foot shock on pharmacokinetics of isosorbide dinitrate orally administered to rats.

Abstract: Abstract-The influence of emotional stress on the pharmacokinetics of isosorbide dinitrate (ISDN) was studied in rats. Plasma levels of orally administered ISDN and metabolites (5-isosorbide mononitrate and 2-isosorbide mononitrate) were lower in rats emotionally stressed by foot shock than in non-stressed control rats. The decrease in the ISDN levels may be mainly due to the delay of drug absorption from the gastrointestinal tract.It is generally recognized that the action of drugs is influenced by various fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…Although potential systemic effects of isosorbide have been shown, 35 we did not observe systemic or contralateral effects of the topical isosorbide application on the left side (unligated side).…”
Section: Discussioncontrasting
confidence: 75%
“…Although potential systemic effects of isosorbide have been shown, 35 we did not observe systemic or contralateral effects of the topical isosorbide application on the left side (unligated side).…”
Section: Discussioncontrasting
confidence: 75%
“…The results showed that the plasma level of ISDN administered non-orally in the ES rats was the same as that in the non-stressed control rats, but plasma levels of the metabolites, 5-ISMN and 2 ISMN, in the ES rats were markedly lower than those in control rats. In the previous study (4), plasma levels of ISDN and its metabolites in ES rats when orally adminis tered was lower than that in non-stressed rats.…”
mentioning
confidence: 71%
“…tional stress, a foot shock loading box was used. The details for the apparatus were described in the previous paper (4).…”
mentioning
confidence: 99%